Novel technique: direct access partial nephrectomy approach through a transperitoneal working space (Roskilde technique). (4th July 2019) - Azawi, Nessn H.; Lindgren, Maria Skydt; Ibsen, Ida Uhrskov; Tolouee, Sara; Nadler, Naomi; Dahl, Claus; Fode, Mikkel
Abstract: Objectives: To describe a direct access partial nephrectomy technique through a transperitoneal working space (Roskilde technique). Materials and methods: Prospective single-center descriptive study between April 2015 and January 2017. The surgical outcomes are evaluated according to the Trifecta criteria (negative margins, warm ischemia time < 20 min and a Clavien-Dindo complication score < 3). Surgical procedure: The same access to the transperitoneal cavity as in a Standard transperitoneal Partial Nephrectomy was used. A direct access was established by incision of the peritoneum directly onto the renal fascia. The renal vessels and tumor were identified and the tumor removed with standard technique. The perinephric fat and peritoneum were then closed with a running suture. Results: In total, 122 patients underwent the Roskilde technique. The mean age was 62.2 years, the median Padua score was 12 (IQR = 9–12) and the median tumor size was 32 mm (IQR = 12–90). The median operative time was 101 min (IQR = 90–125). The trifecta achievement criteria goal was achieved in 116/122 (95%), with a median warm ischemia time of 8 min (IQR = 0-12). Conclusions: The Roskilde technique is safe and feasible. It can be performed on complex renal masses, and it seems to result in short operative times and high Trifecta achievement. Trial registration: None